The Effect of Profitability Ratios on Bank Soundness with GCG Reports as a Moderator: Case Study at PT. BPR BKK Purwodadi (Perseroda) 2020-2024 - Moh Arwan Hamidi; Ngurah Pandji Mertha Agung Durya; Ira Septriana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the extent to which certain profitability ratios, such as ROA and ROE, influence bank health, moderating these variables using Good Corporate Governance reports. A quantitative approach is used in this study, and secondary data from previous years are required for testing, sourced from PT. BPR BKK Purwodadi's report data. These findings demonstrate that companies with high profitability have incentives to maintain bank health, as this reflects effective operational and managerial performance. Furthermore, organizations with good corporate governance (GCG) generally have greater resources and a robust organizational structure, providing them with more opportunities to maximize performance. This study is expected to provide new perspectives on bank health maintenance practices, particularly for business entities in the banking sector. Particularly in the strategically significant banking industry, the results of this study are crucial for authorities such as the Financial Services Authority (OJK) to understand the relationship between corporate profitability, good corporate governance (GCG), and bank health. This understanding helps in developing more appropriate policies to maintain economic stability and financial fairness. The emphasis on business entities in the regional government-owned banking sector (Perseroda) during 2020 to 2024, a dynamic period with economic fluctuations, banking policy transformations, and major geopolitical challenges, distinguishes this study.